A glass fiber-reinforced block copolyamide blend material and a method for preparing the same

CN122978730APending Publication Date: 2026-10-27SHANDONG HIGHDEV NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611097832.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]在熔融共混和注塑成型过程中,上述界面弱结合区会进一步导致玻璃纤维拔出、界面空洞、玻纤外露、制品表面粗糙和翘曲变形

Benefits of technology

[0046]本发明以嵌段共聚酰胺作为基础树脂,通过增强调节聚酰胺提高连续树脂相的承载能力,通过表面浸润处理短切玻璃纤维形成分散增强结构,使共混材料在保持嵌段共聚酰胺柔韧基础的同时,提高拉伸强度、弯曲强度和尺寸支撑能力;本发明采用嵌段型反应界面调节剂同时调节聚酰胺硬段、柔性软段和玻璃纤维表面之间的界面关系,其中聚酰胺相容链段与聚酰胺硬段及增强调节聚酰胺相容,柔性软段相容链段与柔性软段相容,反应性基团与表面浸润处理短切玻璃纤维的表面浸润剂形成界面结合,由断面显微统计结果可知,与未加入嵌段型反应界面调节剂或者仅采用硅烷处理玻璃纤维的对比例相比,所得材料的玻纤拔出孔洞数量和界面空洞面积占比降低,玻纤表面树脂包覆率提高,有利于改善玻璃纤维与嵌段共聚酰胺基体之间的界面结合。本发明通过硅烷偶联剂和聚酰胺型成膜剂对短切玻璃纤维进行表面包覆,能够降低玻璃纤维拔出、界面空洞和玻纤外露的发生程度,提高界面载荷传递能力并改善注塑制品表面状态;本发明制备方法先形成界面预调节熔融树脂相,再侧喂加入表面浸润处理短切玻璃纤维,并通过低剪切分散功能区控制玻璃纤维分散过程,能够降低玻璃纤维断裂和表面浸润剂破坏,使玻璃纤维保持适当残余长度;本发明通过对粒料进行热处理,有助于改善粒料的后续注塑成型稳定性并降低注塑制品的翘曲率,有利于提高成型稳定性并减少制品翘曲。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the technical field of high polymer composite materials, and discloses a glass fiber reinforced block copolyamide blended material and a preparation method thereof. The blended material comprises a block copolyamide, a reinforced adjusting polyamide, surface infiltration treated short glass fibers, a block type reaction interface adjusting agent, a forming flow adjusting agent and a stabilizer. The block type reaction interface adjusting agent comprises a polyamide compatible segment, a flexible soft segment compatible segment and a reactive group. During preparation, an interface pre-adjusting molten resin phase is formed first, the surface infiltration treated short glass fibers are added from the side, and the blended material is obtained through low shear dispersion, exhaust, granulation and heat treatment. The application can improve the interface combination between the glass fibers and the block copolyamide, and improve the material strength and the forming stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer composite materials technology, and more specifically, to a glass fiber reinforced block copolyamide blend material and its preparation method. Background Technology

[0002] Block copolyamide materials are a class of thermoplastic copolyamide materials composed of both hard and flexible polyamide segments. The hard polyamide segments form hard-segment-rich regions, providing the material with strength, wear resistance, and dimensional support; the flexible soft segments form soft-segment-rich regions, providing flexibility, resilience, and low-temperature impact resistance. Due to the synergistic effect between the hard and soft-segment-rich regions, block copolyamide materials possess both the strength of polyamide materials and the flexibility of elastomers, making them valuable for applications in automotive connectors, electronic and electrical protection components, industrial cushioning components, flexible support components, and lightweight injection-molded structural components.

[0003] As these components evolve towards thinner walls, lighter weight, and higher load-bearing capacity, the tensile strength, flexural strength, and long-term dimensional stability under load are insufficient when block copolyamide materials are used alone. Increasing the proportion of hard segments in the polyamide to enhance rigidity can easily reduce the buffering effect of the soft segments, leading to lower notched impact strength and elongation at break. Conversely, increasing the proportion of soft segments to improve toughness and resilience weakens the load-bearing strength and creep resistance. Therefore, simply adjusting the ratio of hard to soft segments in block copolyamide is insufficient to meet the comprehensive requirements of strength, toughness, and molding stability for load-bearing injection molded structural components.

[0004] Glass fiber reinforcement is a common method to improve the strength and dimensional stability of polyamide materials. Existing glass fiber reinforced polyamide materials typically involve adding short-cut or continuous long glass fibers to polyamide 6, polyamide 66, high-temperature polyamides, or bio-based polyamides, allowing the glass fibers to bear external loads and improve material rigidity. However, block copolymers differ from ordinary homogeneous polyamide resins. When glass fibers are directly added to a block copolymer system, the compatibility between the glass fiber surface and the hard and soft segments of the polyamide is not consistent. The glass fibers can easily affect the distribution balance between the hard and soft segment enrichment areas, leading to weak interfacial bonding zones and stress concentration zones within the material.

[0005] During melt blending and injection molding, the aforementioned weak interfacial bonding zones can further lead to glass fiber pull-out, interfacial voids, exposed glass fibers, rough product surfaces, and warping. Using only ordinary silane coupling agents or ordinary maleic anhydride graft compatibilizers typically only improves the localized bonding between the glass fibers and the polyamide matrix, making it difficult to simultaneously address the synergistic relationship between the glass fiber interface, the polyamide hard segment enrichment zone, and the flexible soft segment enrichment zone. Simply increasing the glass fiber content, while further improving the material's flexural modulus, exacerbates the decrease in melt flowability, glass fiber breakage, and loss of impact toughness.

[0006] Therefore, how to improve the interfacial bonding between chopped glass fibers and the block copolyamide matrix, reduce the breakage of glass fibers during melt blending, and take into account the strength, impact toughness and injection molding stability of the material are the technical problems that need to be solved when preparing glass fiber reinforced block copolyamide blends. Summary of the Invention

[0007] The purpose of this invention is to provide a glass fiber reinforced block copolyamide blend material and its preparation method to solve the above-mentioned technical problems.

[0008] To achieve the above objectives, the present invention provides the following solution:

[0009] A glass fiber reinforced block copolyamide blend material, comprising the following components by weight:

[0010] 100 parts of block copolyamide;

[0011] 10-45 parts of polyamide were added to enhance and regulate the effect;

[0012] Surface impregnation treatment with 20-65 parts of chopped glass fiber;

[0013] 2-10 parts of block-type reaction interface modifier;

[0014] 0.5-5 parts of molding flow regulator;

[0015] Stabilizer 0.2-2 parts;

[0016] The block copolyamide includes polyamide hard segments and flexible soft segments;

[0017] The surface wetting agent for the surface-impregnated short glass fibers includes a silane coupling agent and a polyamide film-forming agent;

[0018] The block-type reactive interface modifier includes polyamide segments, flexible segments, and reactive groups, wherein the flexible segments are at least one of polytetrahydrofuran ether segments, polypropylene glycol ether segments, and polyether ester segments.

[0019] Furthermore, the polyamide hard segment accounts for 45-75% by mass in the block copolyamide, and the flexible soft segment accounts for 25-55% by mass in the block copolyamide;

[0020] The polyamide hard segment is at least one of polyamide 6 hard segment, polyamide 66 hard segment, polyamide 610 hard segment, polyamide 612 hard segment and polyamide 12 hard segment;

[0021] The flexible segment is at least one of polytetrahydrofuran ether segment, polypropylene glycol ether segment, and polyether ester segment.

[0022] Furthermore, the reinforcing and regulating polyamide is at least one of polyamide 6, polyamide 66, polyamide 610, and polyamide 612;

[0023] The reinforcing polyamide has a relative viscosity of 2.0-3.0, a melting point of 180-265℃, and a water content of no more than 1500ppm.

[0024] Furthermore, the surface-wetting treated chopped glass fibers are discontinuous glass fibers, and the monofilament diameter of the surface-wetting treated chopped glass fibers is 7-17 μm, and the chopped length is 3-6 mm;

[0025] The silane coupling agent in the surface wetting agent is an aminosilane coupling agent and / or an epoxysilane coupling agent;

[0026] The polyamide film-forming agent is at least one of polyamide oligomers, polyamide waxes, and polyamide emulsions.

[0027] Furthermore, the block-type reaction interface modifier is at least one of epoxy-functionalized flexible segment-polyamide block compatibilizer, oxazoline-functionalized flexible segment-polyamide block compatibilizer, and anhydride-functionalized flexible segment-polyamide block compatibilizer.

[0028] The flexible segment is at least one of polytetrahydrofuran ether segment, polypropylene glycol ether segment, and polyether ester segment;

[0029] The number-average molecular weight of the block-type reaction interface modifier is 9000-25000.

[0030] Further, the reactive group is at least one of epoxy group, oxazoline group, and acid anhydride group; when the reactive group is epoxy group or acid anhydride group, the surface wetting agent contains amino or hydroxyl group; when the reactive group is oxazoline group, the polyamide film-forming agent contains terminal carboxyl group.

[0031] Furthermore, the molding flow regulator includes at least one of amide lubricants, polyamide waxes, low molecular weight polyamides, and hyperbranched polyesters;

[0032] The stabilizer includes at least one of hindered phenolic antioxidants, phosphite antioxidants, and copper salt heat stabilizers.

[0033] Furthermore, after injection molding, the residual length of glass fiber in the injection-molded product of the glass fiber reinforced block copolyamide blend is 0.5-0.9 mm.

[0034] On the other hand, the present invention also provides a method for preparing the above-mentioned glass fiber reinforced block copolyamide blend material, comprising the following steps:

[0035] S1. Dry the block copolyamide and the reinforcing and regulating polyamide separately to obtain the dried resin components;

[0036] S2. The dried resin component, block reactive interface modifier, molding flow modifier and stabilizer are added to the main feed port of the twin-screw extruder, so that the dried resin component and the block reactive interface modifier are melt-mixed in the first stage to obtain the interface pre-conditioned molten resin phase.

[0037] S3. Surface-wetting chopped glass fibers are added to the side feed port of the twin-screw extruder, so that the surface-wetting chopped glass fibers enter the interface pre-conditioned molten resin phase and are dispersed through the low-shear dispersion functional zone to obtain a melt blend.

[0038] S4. The melt blend is subjected to vacuum degassing, extrusion, cooling, pelletizing and drying to obtain granules;

[0039] S5. The granules are heat-treated to obtain a glass fiber reinforced block copolyamide blend.

[0040] Further, in step S1, the drying temperature of the block copolyamide is 70-100℃, and the drying time is 4-8h; the drying temperature of the reinforcing and regulating polyamide is 80-110℃, and the drying time is 4-10h; the moisture content of both the dried block copolyamide and the reinforcing and regulating polyamide is not higher than 0.08%.

[0041] In step S2, the temperature of the first stage of melting and mixing is 220-280℃, and the residence time is 30-150s;

[0042] The twin-screw extruder has a length-to-diameter ratio of 36:1 to 48:1. The twin-screw extruder is provided with a main feeding functional area, a melt plasticizing functional area, an interface pre-conditioning functional area, a glass fiber side feeding functional area, a low shear dispersion functional area, a vacuum exhaust functional area and a metering extrusion functional area in sequence along the material conveying direction.

[0043] The low-shear dispersion functional area is provided with a forward conveying thread element and a low-misalignment forward kneading block. The axial length of the forward conveying thread element accounts for 60-90% of the total axial length of the low-shear dispersion functional area. The misalignment angle of the low-misalignment forward kneading block is 30°-45°. The low-shear dispersion functional area is not provided with a reverse kneading block or a reverse conveying thread element.

[0044] In step S5, the heat treatment temperature is 80-120℃ and the heat treatment time is 2-6h.

[0045] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0046] This invention uses block copolymer polyamide as the base resin. It enhances the load-bearing capacity of the continuous resin phase by reinforcing and regulating the polyamide. By surface-impregnating chopped glass fibers to form a dispersed reinforcing structure, the blend material maintains the flexibility of the block copolymer polyamide while improving tensile strength, flexural strength, and dimensional support. This invention employs a block-type reactive interface modifier to simultaneously regulate the interfacial relationship between the hard segments, flexible segments, and glass fiber surface of the polyamide. Specifically, the polyamide compatible segments are compatible with the hard segments and reinforcing polyamide, the flexible segment compatible segments are compatible with the flexible segments, and the reactive groups form an interfacial bond with the surface-impregnated chopped glass fibers. Cross-sectional microscopic statistics show that, compared to a control group without a block-type reactive interface modifier or with only silane treatment of the glass fibers, the resulting material exhibits a lower number of glass fiber pull-out pores and a lower proportion of interfacial void area, while the resin coating rate on the glass fiber surface is increased. This is beneficial for improving the interfacial bond between the glass fibers and the block copolymer polyamide matrix. This invention utilizes silane coupling agents and polyamide film-forming agents to surface-coat chopped glass fibers, reducing the occurrence of glass fiber pull-out, interfacial voids, and glass fiber exposure, thereby improving interfacial load transfer capacity and the surface condition of injection-molded products. The preparation method of this invention first forms an interfacial pre-conditioned molten resin phase, then side-feeds surface-wetting chopped glass fibers, and controls the glass fiber dispersion process through a low-shear dispersion functional zone, reducing glass fiber breakage and surface wetting agent degradation, ensuring the glass fibers maintain an appropriate residual length. Furthermore, the heat treatment of the granules helps improve the subsequent injection molding stability of the granules and reduces the warpage of injection-molded products, thus enhancing molding stability and reducing product warpage. Detailed Implementation

[0047] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0048] In the following embodiments, the block-type reactive interface modifier is a pre-prepared functionalized block compatibilizer, which includes polyamide segments, flexible segments, and reactive groups. The polyamide segments, flexible segments, reactive groups, and number-average molecular weights used in different embodiments are determined according to the corresponding embodiments.

[0049] Example 1

[0050] This embodiment provides a glass fiber reinforced block copolyamide blend material, which includes, by weight: 100 parts block copolyamide, 25 parts reinforcing and regulating polyamide, 40 parts surface-impregnated chopped glass fiber, 5 parts block reactive interface regulator, 1.5 parts molding flow regulator, and 0.8 parts stabilizer.

[0051] The block copolymer amide is a polyamide 12-polytetrahydrofuran ether block copolymer, with polyamide 12 hard segments accounting for 60% by mass and polytetrahydrofuran ether soft segments accounting for 40% by mass. The reinforcing and regulating polyamide is polyamide 66, with a relative viscosity of 2.6, a melting point of 260℃, and a moisture content not exceeding 1500ppm. The surface-wetting treated chopped glass fibers are alkali-free E-glass chopped glass fibers with a single filament diameter of 13μm and a chopped length of 4.5mm; its surface wetting agent includes 3-aminopropyltriethoxysilane and carboxyl-terminated polyamide 12 oligomers. The carboxyl-terminated polyamide 12 oligomers, as polyamide-type film-forming agents, have a number average molecular weight of 2500 and an acid value of 35mgKOH / g.

[0052] The block-type reaction interface modifier is an epoxy-functionalized polytetrahydrofuran ether-polyamide 12 block compatibilizer with a number-average molecular weight of 12,000. The molding flow modifier is a dimer acid type polyamide wax with a softening point of 135°C, an acid value of 5 mg KOH / g, and an amine value of 3 mg KOH / g. The stabilizer includes 0.4 parts of hindered phenolic antioxidant N,N'-hexane-1,6-dimethylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide] and 0.4 parts of phosphite antioxidant tris(2,4-di-tert-butylphenyl) phosphite.

[0053] In the preparation process, the block copolyamide was dried at 90°C for 6 hours, and the reinforcing and conditioning polyamide was dried at 100°C for 8 hours to obtain a dried resin component. The dried resin component, block-type reactive interface modifier, molding flow modifier, and stabilizer were added to the main feed port of a twin-screw extruder, and a first-stage melt mixing was performed at 270°C with a residence time of 90 seconds to obtain an interface-preconditioned molten resin phase. Surface-wetted chopped glass fibers were added through the side feed port of the twin-screw extruder, allowing them to enter the interface-preconditioned molten resin phase and dispersed through a low-shear dispersion zone to obtain a melt blend. The melt blend was subjected to vacuum degassing, extrusion, cooling, pelletizing, and drying to obtain granules. The granules were heat-treated at 100°C for 4 hours to obtain a glass fiber reinforced block copolyamide blend.

[0054] In this embodiment, the twin-screw extruder has a length-to-diameter ratio of 40:1. Along the material conveying direction, it is sequentially configured with a main feeding zone, a melt plasticizing zone, an interface pre-conditioning zone, a glass fiber side feeding zone, a low-shear dispersion zone, a vacuum exhaust zone, and a metering extrusion zone. The low-shear dispersion zone is equipped with a forward conveying threaded element and a low-staggered-angle forward kneading block. The axial length of the forward conveying threaded element accounts for 75% of the total axial length of the low-shear dispersion zone. The staggered angle of the low-staggered-angle forward kneading block is 30°. The low-shear dispersion zone does not have a reverse kneading block or a reverse conveying threaded element.

[0055] Example 2

[0056] This embodiment provides a glass fiber reinforced block copolyamide blend material, which includes, by weight: 100 parts block copolyamide, 10 parts reinforcing and regulating polyamide, 20 parts surface-impregnated chopped glass fiber, 2 parts block reactive interface regulator, 0.5 parts molding flow regulator, and 0.2 parts stabilizer.

[0057] The block copolymer is a polyamide 6-polypropylene glycol ether block copolymer, with polyamide 6 hard segments comprising 55% by mass and polypropylene glycol ether soft segments comprising 45% by mass. The reinforcing and regulating polyamide is polyamide 6 with a relative viscosity of 2.4, a melting point of 220℃, and a moisture content not exceeding 1500ppm. The surface-wetting treated chopped glass fibers are alkali-free E-glass chopped glass fibers with a monofilament diameter of 10μm and a chopped length of 3mm. The surface wetting agent includes 3-glycidyl etheroxypropyltrimethoxysilane and an aqueous emulsion of polyamide 6. The aqueous emulsion of polyamide 6 containing terminal carboxyl groups serves as a polyamide-type film-forming agent with a solid content of 30%, and the D50 particle size of the polyamide 6 particles in the emulsion is 0.4μm.

[0058] The block-type reaction interface modifier is an oxazoline-functionalized polypropylene glycol ether-polyamide 6 block compatibilizer with a number average molecular weight of 9000. The molding flow modifier is ethylene bis-stearamide. The stabilizers include 0.1 parts of hindered phenolic antioxidant N,N'-hexane-1,6-dimethylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide] and 0.1 parts of phosphite antioxidant tris(2,4-di-tert-butylphenyl) phosphite.

[0059] In the preparation process, the block copolyamide was dried at 80°C for 6 hours, and the reinforcing and conditioning polyamide was dried at 90°C for 6 hours to obtain a dried resin component. The dried resin component, block-type reactive interface modifier, molding flow modifier, and stabilizer were added to the main feed port of a twin-screw extruder, and the first stage of melt mixing was carried out at 230°C with a residence time of 60 seconds to obtain an interface-pre-conditioned molten resin phase. Surface-wetted chopped glass fibers were added through the side feed port of the twin-screw extruder, dispersed through the low-shear dispersion zone, and then subjected to vacuum degassing, extrusion, cooling, pelletizing, and drying to obtain granules. The granules were heat-treated at 90°C for 5 hours to obtain a glass fiber reinforced block copolyamide blend.

[0060] In this embodiment, the length-to-diameter ratio of the twin-screw extruder is 36:1, the axial length of the forward conveying thread element in the low-shear dispersion functional zone accounts for 80% of the total axial length of the low-shear dispersion functional zone, the stagger angle of the low-staggered forward kneading block is 30°, and the low-shear dispersion functional zone does not have a reverse kneading block or a reverse conveying thread element.

[0061] Example 3

[0062] This embodiment provides a glass fiber reinforced block copolyamide blend material, which includes, by weight: 100 parts block copolyamide, 45 parts reinforcing and regulating polyamide, 65 parts surface-impregnated chopped glass fiber, 10 parts block reactive interface regulator, 5 parts molding flow regulator, and 2 parts stabilizer.

[0063] The block copolymer is a polyamide 610-polyether ester block copolymer, with polyamide 610 hard segments comprising 65% by mass and polyether ester soft segments comprising 35% by mass. The reinforcing and regulating polyamide is composed of polyamide 610 and polyamide 612, with a mass ratio of 1:1. Polyamide 610 has a relative viscosity of 2.3, a melting point of 220℃, and a moisture content not exceeding 1500ppm; polyamide 612 has a relative viscosity of 2.2, a melting point of 215℃, and a moisture content not exceeding 1500ppm. The surface-impregnated chopped glass fiber is alkali-free E-glass chopped glass fiber with a single filament diameter of 17μm and a chopped length of 6mm. Its surface wetting agent includes 3-aminopropyltriethoxysilane and a film-forming dimer acid type polyamide wax, wherein the film-forming dimer acid type polyamide wax has a softening point of 125℃ and an acid value of 8mgKOH / g.

[0064] The block-type reaction interface modifier is an anhydride-functionalized polyether ester-polyamide 610 block compatibilizer with a number average molecular weight of 18,000. The molding flow modifier is a hydroxyl-terminated hyperbranched polyester with a number average molecular weight of 2,500 and a hydroxyl value of 480 mg KOH / g. The stabilizer includes 0.5 parts of hindered phenolic antioxidant N,N'-hexane-1,6-dimethylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], 0.5 parts of phosphite antioxidant tris(2,4-di-tert-butylphenyl) phosphite, and 1 part of cuprous iodide-potassium iodide compound heat stabilizer, with a mass ratio of cuprous iodide to potassium iodide of 1:10.

[0065] In the preparation process, the block copolyamide was dried at 100℃ for 6 hours, and polyamide 610 and polyamide 612 were dried at 105℃ for 8 hours to obtain a dried resin component. The dried resin component, block-type reactive interface modifier, molding flow modifier, and stabilizer were added to the main feed port of a twin-screw extruder, and the first stage of melt mixing was carried out at 260℃ with a residence time of 120 seconds to obtain an interface-pre-conditioned molten resin phase. Surface-wetted chopped glass fibers were added from the side feed port of the twin-screw extruder, dispersed through the low-shear dispersion zone, and then subjected to vacuum degassing, extrusion, cooling, pelletizing, and drying to obtain granules. The granules were heat-treated at 120℃ for 2 hours to obtain a glass fiber reinforced block copolyamide blend.

[0066] In this embodiment, the length-to-diameter ratio of the twin-screw extruder is 48:1, the axial length of the forward conveying thread element in the low-shear dispersion functional zone accounts for 60% of the total axial length of the low-shear dispersion functional zone, the stagger angle of the low-staggered forward kneading block is 45°, and the low-shear dispersion functional zone does not have a reverse kneading block or a reverse conveying thread element.

[0067] Example 4

[0068] This embodiment provides a glass fiber reinforced block copolyamide blend material, which includes, by weight: 100 parts block copolyamide, 35 parts reinforcing and regulating polyamide, 50 parts surface-impregnated chopped glass fiber, 7 parts block reactive interface regulator, 2 parts molding flow regulator, and 1.2 parts stabilizer.

[0069] The block copolymer amide is a polyamide 66-polytetrahydrofuran ether block copolymer, with polyamide 66 hard segments accounting for 70% by mass and polytetrahydrofuran ether soft segments accounting for 30% by mass. The reinforcing and regulating polyamide is polyamide 66 with a relative viscosity of 2.6, a melting point of 260℃, and a moisture content not exceeding 1500ppm. The surface-wetting treated chopped glass fibers are alkali-free E-glass chopped glass fibers with a single filament diameter of 13μm and a chopped length of 4.5mm. The surface wetting agent includes 3-aminopropyltriethoxysilane and carboxyl-terminated polyamide 12 oligomers. The carboxyl-terminated polyamide 12 oligomers, as polyamide-type film-forming agents, have a number-average molecular weight of 2500 and an acid value of 35mgKOH / g.

[0070] The block-type reaction interface modifier is an epoxy-functionalized polytetrahydrofuran ether-polyamide 66 block compatibilizer with a number-average molecular weight of 25,000. The molding flow modifier is a dimer acid type polyamide wax with a softening point of 135°C, an acid value of 5 mgKOH / g, and an amine value of 3 mgKOH / g. The stabilizer includes 0.4 parts of hindered phenolic antioxidant N,N'-hexane-1,6-dimethylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], 0.4 parts of phosphite antioxidant tris(2,4-di-tert-butylphenyl) phosphite, and 0.4 parts of cuprous iodide-potassium iodide compound heat stabilizer, with a mass ratio of cuprous iodide to potassium iodide of 1:10.

[0071] In the preparation process, the block copolyamide was dried at 90℃ for 8 hours, and the reinforcing and conditioning polyamide was dried at 110℃ for 8 hours to obtain a dried resin component. The dried resin component, block-type reactive interface modifier, molding flow modifier, and stabilizer were added to the main feed port of a twin-screw extruder, and the first stage of melt mixing was carried out at 270℃ with a residence time of 100 seconds to obtain an interface-pre-conditioned molten resin phase. Surface-wetted chopped glass fibers were added from the side feed port of the twin-screw extruder, dispersed through the low-shear dispersion zone, and then subjected to vacuum degassing, extrusion, cooling, pelletizing, and drying to obtain granules. The granules were heat-treated at 110℃ for 4 hours to obtain a glass fiber reinforced block copolyamide blend.

[0072] In this embodiment, the length-to-diameter ratio of the twin-screw extruder is 44:1, the axial length of the forward conveying thread element in the low-shear dispersion functional zone accounts for 70% of the total axial length of the low-shear dispersion functional zone, the stagger angle of the low-staggered forward kneading block is 45°, and the low-shear dispersion functional zone does not have a reverse kneading block or a reverse conveying thread element.

[0073] Example 5

[0074] This embodiment provides a glass fiber reinforced block copolyamide blend material, which includes, by weight: 100 parts block copolyamide, 15 parts reinforcing and regulating polyamide, 35 parts surface-impregnated chopped glass fiber, 4 parts block reactive interface regulator, 2 parts molding flow regulator, and 0.6 parts stabilizer.

[0075] The block copolymer amide is a polyamide 12-polytetrahydrofuran ether block copolymer, with polyamide 12 hard segments accounting for 60% by mass and polytetrahydrofuran ether soft segments accounting for 40% by mass. The reinforcing and regulating polyamide is polyamide 610, with a relative viscosity of 2.3, a melting point of 220℃, and a water content not exceeding 1500ppm. The surface-wetting treated chopped glass fibers are alkali-free E-glass chopped glass fibers with a single filament diameter of 10μm and a chopped length of 3mm; its surface wetting agent includes 3-glycidyl etheroxypropyltrimethoxysilane and an amino-terminated polyamide 6 aqueous emulsion, wherein the polyamide 6 aqueous emulsion, as a polyamide-type film-forming agent, has a solid content of 30%, and the D50 particle size of the polyamide 6 particles in the emulsion is 0.4μm.

[0076] The block-type reaction interface modifier is an epoxy-functionalized polytetrahydrofuran ether-polyamide 12 block compatibilizer with a number-average molecular weight of 12,000. The molding flow modifier comprises 1 part ethylene bis-stearamide and 1 part dimer acid type polyamide wax, wherein the dimer acid type polyamide wax has a softening point of 135℃, an acid value of 5 mgKOH / g, and an amine value of 3 mgKOH / g. The stabilizer comprises 0.3 parts hindered phenolic antioxidant N,N'-hexane-1,6-dimethylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide] and 0.3 parts phosphite antioxidant tris(2,4-di-tert-butylphenyl) phosphite.

[0077] In the preparation process, the block copolyamide was dried at 85°C for 7 hours, and the reinforcing and conditioning polyamide was dried at 95°C for 7 hours to obtain a dried resin component. The dried resin component, block-type reactive interface modifier, molding flow modifier, and stabilizer were added to the main feed port of a twin-screw extruder, and the first stage of melt mixing was carried out at 240°C with a residence time of 80 seconds to obtain an interface-pre-conditioned molten resin phase. Surface-wetted chopped glass fibers were added through the side feed port of the twin-screw extruder, dispersed through the low-shear dispersion zone, and then subjected to vacuum degassing, extrusion, cooling, pelletizing, and drying to obtain granules. The granules were heat-treated at 95°C for 4 hours to obtain a glass fiber reinforced block copolyamide blend.

[0078] In this embodiment, the length-to-diameter ratio of the twin-screw extruder is 40:1, the axial length of the forward conveying thread element in the low-shear dispersion functional zone accounts for 90% of the total axial length of the low-shear dispersion functional zone, the stagger angle of the low-staggered forward kneading block is 30°, and the low-shear dispersion functional zone does not have a reverse kneading block or a reverse conveying thread element.

[0079] Example 6

[0080] This embodiment provides a glass fiber reinforced block copolyamide blend material, which includes, by weight: 100 parts block copolyamide, 40 parts reinforcing and regulating polyamide, 60 parts surface-impregnated chopped glass fiber, 8 parts block reactive interface regulator, 4 parts molding flow regulator, and 1.5 parts stabilizer.

[0081] The block copolymer amide is a polyamide 610-polyether ester block copolymer, with polyamide 610 hard segments comprising 65% by mass and polyether ester soft segments comprising 35% by mass. The reinforcing and regulating polyamide is polyamide 612, with a relative viscosity of 2.2, a melting point of 215℃, and a moisture content not exceeding 1500ppm. The surface-wetting treated chopped glass fibers are alkali-free E-glass chopped glass fibers with a single filament diameter of 17μm and a chopped length of 6mm; the surface wetting agent includes 3-aminopropyltriethoxysilane and a film-forming dimer acid type polyamide wax, wherein the film-forming dimer acid type polyamide wax has a softening point of 125℃ and an acid value of 8mgKOH / g.

[0082] The block-type reaction interface modifier is an anhydride-functionalized polyether ester-polyamide 610 block compatibilizer with a number-average molecular weight of 18,000. The molding flow modifier comprises 2 parts of dimer acid type polyamide wax and 2 parts of hydroxyl-terminated hyperbranched polyester; the dimer acid type polyamide wax has a softening point of 135℃, an acid value of 5 mgKOH / g, and an amine value of 3 mgKOH / g; the hydroxyl-terminated hyperbranched polyester has a number-average molecular weight of 2,500 and a hydroxyl value of 480 mgKOH / g. The stabilizer comprises 0.5 parts of hindered phenolic antioxidant N,N'-hexane-1,6-dimethylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], 0.5 parts of phosphite antioxidant tris(2,4-di-tert-butylphenyl) phosphite, and 0.5 parts of cuprous iodide-potassium iodide compound heat stabilizer, with a cuprous iodide to potassium iodide mass ratio of 1:10.

[0083] In the preparation process, the block copolyamide was dried at 95°C for 8 hours, and the reinforcing and conditioning polyamide was dried at 100°C for 8 hours to obtain a dried resin component. The dried resin component, block-type reactive interface modifier, molding flow modifier, and stabilizer were added to the main feed port of a twin-screw extruder, and the first stage of melt mixing was carried out at 255°C with a residence time of 110 seconds to obtain an interface-pre-conditioned molten resin phase. Surface-wetted chopped glass fibers were added through the side feed port of the twin-screw extruder, dispersed through the low-shear dispersion zone, and then subjected to vacuum degassing, extrusion, cooling, pelletizing, and drying to obtain granules. The granules were heat-treated at 115°C for 3 hours to obtain a glass fiber reinforced block copolyamide blend.

[0084] In this embodiment, the length-to-diameter ratio of the twin-screw extruder is 48:1, the axial length of the forward conveying thread element in the low-shear dispersion functional zone accounts for 65% of the total axial length of the low-shear dispersion functional zone, the stagger angle of the low-staggered forward kneading block is 45°, and the low-shear dispersion functional zone does not have a reverse kneading block or a reverse conveying thread element.

[0085] Comparative Example 1

[0086] The difference between this comparative example and Example 1 is that no block-type reaction interface modifier is added. Specifically, this comparative example includes, by weight, 100 parts of polyamide 12-polytetrahydrofuran ether block copolymer, 25 parts of polyamide 66, 40 parts of surface-impregnated chopped glass fibers, 1.5 parts of dimer acid type polyamide wax, 0.4 parts of hindered phenolic antioxidant N,N'-hexane-1,6-dimethylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], and 0.4 parts of phosphite antioxidant tris(2,4-di-tert-butylphenyl) phosphite. The dimer acid type polyamide wax has a softening point of 135°C, an acid value of 5 mg KOH / g, and an amine value of 3 mg KOH / g; the surface-impregnation treatment of the chopped glass fibers and the preparation steps are the same as in Example 1.

[0087] Comparative Example 2

[0088] The difference between this comparative example and Example 1 is that the epoxy-functionalized polytetrahydrofuran ether-polyamide 12 block compatibilizer in Example 1 is replaced with maleic anhydride-grafted ethylene-octene copolymer. The maleic anhydride grafting rate of the maleic anhydride-grafted ethylene-octene copolymer is 0.8%, the melt flow rate is 2.0 g / 10 min, the test conditions are 190 °C and 2.16 kg, and the amount used is still 5 parts. The remaining raw materials and preparation steps are the same as in Example 1.

[0089] Comparative Example 3

[0090] The difference between this comparative example and Example 1 is that the surface-wetting treated chopped glass fibers in Example 1 are replaced with ordinary alkali-free E-glass chopped glass fibers. The ordinary alkali-free E-glass chopped glass fibers have a single filament diameter of 13 μm and a chopped length of 4.5 mm. Their surface treatment agent contains only 3-aminopropyltriethoxysilane and does not contain polyamide film-forming agents. The remaining raw materials and preparation steps are the same as in Example 1.

[0091] Comparative Example 4

[0092] The difference between this comparative example and Example 1 is that the surface-wetting treated chopped glass fibers from Example 1, along with polyamide 12-polytetrahydrofuran ether block copolymer, polyamide 66, epoxy-functionalized polytetrahydrofuran ether-polyamide 12 block compatibilizer, dimer acid type polyamide wax, hindered phenolic antioxidant N,N'-hexane-1,6-dimethylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide] and phosphite antioxidant tris(2,4-di-tert-butylphenyl) phosphite, are added from the main feed port of a twin-screw extruder, instead of using a glass fiber side-feed method. The remaining subsequent processing steps are the same as in Example 1.

[0093] Comparative Example 5

[0094] The difference between this comparative example and Example 1 is that the low-shear dispersion zone of the twin-screw extruder is equipped with a reverse kneading block, and the forward kneading block with a staggered angle of 30° in Example 1 is replaced with a forward kneading block with a staggered angle of 60°. The remaining raw materials and preparation steps are the same as in Example 1.

[0095] Comparative Example 6

[0096] The difference between this comparative example and Example 1 is that no heat treatment of the pellets is performed after extrusion, cooling, pelletizing, and drying. The remaining raw materials and preparation steps are the same as in Example 1.

[0097] Comparative Example 7

[0098] The difference between this comparative example and Example 1 is that no reinforcing polyamide is added. Specifically, this comparative example comprises, by weight, 100 parts of polyamide 12-polytetrahydrofuran ether block copolymer, 40 parts of surface-impregnated chopped glass fibers, 5 parts of epoxy-functionalized polytetrahydrofuran ether-polyamide 12 block compatibilizer, 1.5 parts of dimer acid type polyamide wax, 0.4 parts of hindered phenolic antioxidant N,N'-hexane-1,6-dimethylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], and 0.4 parts of phosphite antioxidant tris(2,4-di-tert-butylphenyl) phosphite. The dimer acid type polyamide wax has a softening point of 135°C, an acid value of 5 mg KOH / g, and an amine value of 3 mg KOH / g; the surface-impregnated chopped glass fibers and the preparation steps are the same as in Example 1.

[0099] The relative viscosity, melting point, moisture content, number-average molecular weight, softening point, acid value, amine value, hydroxyl value, solid content, and D50 particle size listed in the above examples and comparative examples are all test values ​​for the corresponding raw materials. The moisture content was determined using the Karl Fischer method.

[0100] The blends obtained in Examples 1-6 and Comparative Examples 1-7 were injection molded to prepare standard test strips and injection-molded flat samples. Examples 1 and Comparative Examples 1-7 used the same granule drying conditions, injection molding conditions, and sample condition conditioning conditions; Examples 2-6 used injection molding temperatures adapted to the melting points of their matrix resins, and their performance was tested according to the same test standards.

[0101] Tensile strength and elongation at break shall be tested according to GB / T 1040.2; flexural strength and flexural modulus shall be tested according to GB / T 9341; notched impact strength shall be tested according to GB / T 1843. At least five parallel samples shall be tested for each property, and the arithmetic mean shall be taken. The warpage test method is as follows: place the injection-molded flat sample on a horizontal reference surface, measure the maximum warpage height of the sample relative to the reference surface, and calculate the warpage rate according to the ratio of the maximum warpage height to the length of the sample in the corresponding direction.

[0102] The residual glass fiber length was determined using the ashing statistical method. A sample from the middle of the injection-molded product was taken as the test sample. After ashing the resin matrix, the residual glass fibers were collected. The lengths of at least 200 glass fibers were counted using an optical microscope, and the arithmetic mean of the counted glass fiber lengths was taken as the residual glass fiber length.

[0103] Interface defects were determined using a scanning electron microscope (SEM) cross-sectional statistical method. Injection-molded samples were subjected to low-temperature brittle fracture, and the fracture surfaces were sputter-coated with gold and observed at 500x magnification. Five fields of view were randomly selected for each sample, and the number of fiberglass pull-out holes, the proportion of interface void area, and the resin coating rate on the fiberglass surface were statistically analyzed, with the arithmetic mean taken. The number of fiberglass pull-out holes was expressed as the number of identifiable fiberglass pull-out holes per unit cross-sectional area; the proportion of interface void area was the ratio of the interface void area to the total area of ​​the observation area; and the resin coating rate on the fiberglass surface was the ratio of the visible circumferential resin adhesion length to the observable circumferential length of the fiberglass.

[0104] Table 1 Mechanical properties, molding stability and residual glass fiber length

[0105] sample Tensile strength / MPa Bending strength / MPa Flexural modulus / GPa <![CDATA[Notched impact strength / kJ·m -2 > Elongation at break / % Warpage rate / % Fiberglass residual length / mm Example 1 84 136 4.4 12.2 5.4 0.54 0.7 Example 2 58 92 2.8 16.4 9.2 0.38 0.52 Example 3 106 170 5.8 9.6 3.9 0.72 0.86 Example 4 112 178 6.1 9.1 3.6 0.76 0.78 Example 5 76 123 3.9 13.1 6.2 0.51 0.61 Example 6 101 162 5.6 10 4.1 0.73 0.82 Comparative Example 1 66 112 4 7.9 3.7 0.82 0.67 Comparative Example 2 72 119 4.1 8.9 4.1 0.74 0.68 Comparative Example 3 69 115 4 8.5 3.9 0.78 0.66 Comparative Example 4 70 117 3.8 8.6 4 0.75 0.39 Comparative Example 5 73 122 4 8.1 3.7 0.8 0.34 Comparative Example 6 80 130 4.3 11.3 5 0.64 0.69 Comparative Example 7 61 101 3.5 11.6 6.8 0.61 0.68

[0106] Table 2 Statistical Results of Interface Defects

[0107] sample <![CDATA[Number of glass fiber pulled-out holes / piece·mm -2 > Percentage of void area in the interface / % Resin coating rate on fiberglass surface / % Example 1 32 3.3 67 Example 2 29 3 69 Example 3 39 4 62 Example 4 41 4.2 60 Example 5 34 3.5 65 Example 6 40 4.1 61 Comparative Example 1 59 6.3 47 Comparative Example 2 49 5.2 54 Comparative Example 3 54 5.7 50 Comparative Example 4 50 5.3 52 Comparative Example 5 57 6 48 Comparative Example 6 43 4.5 58 Comparative Example 7 46 4.8 56

[0108] As shown in Tables 1 and 2, the tensile strength, flexural strength, and notched impact strength of Example 1 were 84 MPa, 136 MPa, and 12.2 kJ·m⁻², respectively. The number of glass fiber pull-out holes, the proportion of interfacial void area, and the resin coating rate on the glass fiber surface were 32 holes·mm⁻², 3.3%, and 67%, respectively. Comparative Example 1, without the addition of a block-type reactive interface modifier, had corresponding mechanical properties of 66 MPa, 112 MPa, and 7.9 kJ·m⁻², respectively, and corresponding interfacial defect statistics of 59 holes·mm⁻², 6.3%, and 47%, respectively. Since the difference between Example 1 and Comparative Example 1 lies in the addition of a block-type reactive interface modifier, the above results indicate that under the system and test conditions described in this example, the addition of the block-type reactive interface modifier reduces interfacial defects and improves resin adhesion to the glass fiber surface, corresponding to increases in tensile strength, flexural strength, and notched impact strength.

[0109] Comparative Example 2 used 5 parts of maleic anhydride-grafted ethylene-octene copolymer instead of the 5 parts of epoxy-functionalized polytetrahydrofuran ether-polyamide 12 block compatibilizer in Example 1. The tensile strength, flexural strength, and notched impact strength of Comparative Example 2 were 72 MPa, 119 MPa, and 8.9 kJ·m⁻², respectively, and the interfacial void area ratio and glass fiber surface resin coating rate were 5.2% and 54%, respectively, all of which failed to achieve the corresponding results of Example 1. This comparative result indicates that, under the same raw material dosage and other process conditions, the block-type reactive interface modifier used in this example achieved a lower interfacial void area ratio and a higher glass fiber surface resin coating rate, and also exhibited superior mechanical properties.

[0110] The surface treatment agent used in Comparative Example 3 contained only 3-aminopropyltriethoxysilane and no polyamide film-forming agent. Its tensile strength, flexural strength, and notched impact strength were 69 MPa, 115 MPa, and 8.5 kJ·m⁻², respectively, with an interfacial void area ratio of 5.7% and a glass fiber surface resin coating rate of 50%. Under the same conditions of other raw materials and preparation steps, Example 1 showed higher mechanical properties and glass fiber surface resin coating rate, and a lower interfacial void area ratio. This indicates that in this example system, treating the glass fiber with a wetting agent containing both a silane coupling agent and a polyamide film-forming agent is beneficial for improving the interfacial state between the glass fiber and the block copolyamide matrix.

[0111] Example 1 uses a glass fiber side-feeding method and a low-shear dispersion zone, with a glass fiber residual length of 0.70 mm; Comparative Example 4 uses a glass fiber main-feeding method, with a glass fiber residual length of 0.39 mm; Comparative Example 5 sets a reverse kneading block in the low-shear dispersion zone and uses a forward kneading block with a staggered angle of 60°, with a glass fiber residual length of 0.34 mm. The above results indicate that under the processing conditions of this example, the glass fiber side-feeding method and the dispersion method of not setting a reverse element and using a forward kneading block with a low staggered angle can reduce excessive breakage of glass fibers during melt processing.

[0112] Comparative Example 6, without granule heat treatment, exhibited tensile strength, flexural strength, notched impact strength, and warpage of 80 MPa, 130 MPa, 11.3 kJ·m⁻², and 0.64%, respectively. Example 1, after heat treatment at 100°C for 4 hours, showed corresponding results of 84 MPa, 136 MPa, 12.2 kJ·m⁻², and 0.54%. Under otherwise identical conditions, these results demonstrate that the granule heat treatment employed in this example helps reduce the warpage of the subsequently injection-molded flat sample.

[0113] Comparative Example 7, without the addition of reinforcing polyamide, exhibited tensile strength, flexural strength, and flexural modulus of 61 MPa, 101 MPa, and 3.5 GPa, respectively; the corresponding results for Example 1 were 84 MPa, 136 MPa, and 4.4 GPa. These results demonstrate that the addition of reinforcing polyamide to the system in this example improved the tensile strength, flexural strength, and flexural modulus of the material.

[0114] In Example 2, the glass fiber content was 20 parts, and its notched impact strength and elongation at break were 16.4 kJ·m⁻² and 9.2%, respectively. In Example 3, the glass fiber content was 65 parts, and its tensile strength, flexural strength, and flexural modulus were 106 MPa, 170 MPa, and 5.8 GPa, respectively. Examples 1, 4, 5, and 6 used different combinations of block copolyamide, reinforcing polyamide, surface-wetting treated chopped glass fiber, and block-type reactive interface modifier, and all obtained corresponding mechanical properties, interface defect statistics, and glass fiber residual length data, indicating that the components and preparation methods can be used in different block copolyamide systems.

[0115] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made to the technical solutions of the present invention by those skilled in the art without departing from the spirit of the present invention should fall within the protection scope defined by the present invention.

Claims

1. A glass fiber reinforced block copolyamide blend material, characterized in that, By weight, it includes the following components: 100 parts of block copolyamide; 10-45 parts of polyamide were added to enhance and regulate the effect; Surface impregnation treatment with 20-65 parts of chopped glass fiber; 2-10 parts of block-type reaction interface modifier; 0.5-5 parts of molding flow regulator; Stabilizer 0.2-2 parts; The block copolyamide includes polyamide hard segments and flexible soft segments; The surface wetting agent for the surface-impregnated short glass fibers includes a silane coupling agent and a polyamide film-forming agent; The block-type reactive interface modifier includes polyamide segments, flexible segments, and reactive groups, wherein the flexible segments are at least one of polytetrahydrofuran ether segments, polypropylene glycol ether segments, and polyether ester segments.

2. The glass fiber reinforced block copolyamide blend material according to claim 1, characterized in that, The polyamide hard segment accounts for 45-75% of the mass of the block copolyamide, and the flexible soft segment accounts for 25-55% of the mass of the block copolyamide. The polyamide hard segment is at least one of polyamide 6 hard segment, polyamide 66 hard segment, polyamide 610 hard segment, polyamide 612 hard segment and polyamide 12 hard segment; The flexible segment is at least one of polytetrahydrofuran ether segment, polypropylene glycol ether segment, and polyether ester segment.

3. The glass fiber reinforced block copolyamide blend material according to claim 1, characterized in that, The reinforcing and regulating polyamide is at least one of polyamide 6, polyamide 66, polyamide 610, and polyamide 612; The reinforcing polyamide has a relative viscosity of 2.0-3.0, a melting point of 180-265℃, and a water content of no more than 1500ppm.

4. The glass fiber reinforced block copolyamide blend material according to claim 1, characterized in that, The surface-wetting treated chopped glass fibers are discontinuous glass fibers, with a single filament diameter of 7-17 μm and a chopped length of 3-6 mm. The silane coupling agent in the surface wetting agent is an aminosilane coupling agent and / or an epoxysilane coupling agent; The polyamide film-forming agent is at least one of polyamide oligomers, polyamide waxes, and polyamide emulsions.

5. The glass fiber reinforced block copolyamide blend material according to claim 1, characterized in that, The block-type reaction interface modifier is at least one of epoxy-functionalized flexible segment-polyamide block compatibilizer, oxazoline-functionalized flexible segment-polyamide block compatibilizer, and anhydride-functionalized flexible segment-polyamide block compatibilizer. The flexible segment is at least one of polytetrahydrofuran ether segment, polypropylene glycol ether segment, and polyether ester segment; The number-average molecular weight of the block-type reaction interface modifier is 9000-25000.

6. The glass fiber reinforced block copolyamide blend material according to claim 1, characterized in that, The reactive group is at least one of epoxy, oxazoline, and acid anhydride groups; when the reactive group is epoxy or acid anhydride, the surface wetting agent contains amino or hydroxyl groups; when the reactive group is oxazoline, the polyamide film-forming agent contains terminal carboxyl groups.

7. The glass fiber reinforced block copolyamide blend material according to claim 1, characterized in that, The molding flow modifier includes at least one of amide lubricants, polyamide waxes, low molecular weight polyamides, and hyperbranched polyesters; The stabilizer includes at least one of hindered phenolic antioxidants, phosphite antioxidants, and copper salt heat stabilizers.

8. The glass fiber reinforced block copolyamide blend material according to claim 1, characterized in that, After injection molding, the residual glass fiber length in the glass fiber reinforced block copolyamide blend is 0.5-0.9 mm.

9. A method for preparing the glass fiber reinforced block copolyamide blend material according to any one of claims 1-8, characterized in that, Includes the following steps: S1. Dry the block copolyamide and the reinforcing and regulating polyamide separately to obtain the dried resin components; S2. The dried resin component, block reactive interface modifier, molding flow modifier and stabilizer are added to the main feed port of the twin-screw extruder, so that the dried resin component and the block reactive interface modifier are melt-mixed in the first stage to obtain the interface pre-conditioned molten resin phase. S3. Surface-wetting chopped glass fibers are added to the side feed port of the twin-screw extruder, so that the surface-wetting chopped glass fibers enter the interface pre-conditioned molten resin phase and are dispersed through the low-shear dispersion functional zone to obtain a melt blend. S4. The melt blend is subjected to vacuum degassing, extrusion, cooling, pelletizing and drying to obtain granules; S5. The granules are heat-treated to obtain a glass fiber reinforced block copolyamide blend.

10. The method according to claim 9, characterized in that, In step S1, the drying temperature of the block copolyamide is 70-100℃, and the drying time is 4-8 hours; the drying temperature of the reinforcing and regulating polyamide is 80-110℃, and the drying time is 4-10 hours; the moisture content of both the dried block copolyamide and the reinforcing and regulating polyamide is not higher than 0.08%. In step S2, the temperature of the first stage of melting and mixing is 220-280℃, and the residence time is 30-150s; The twin-screw extruder has a length-to-diameter ratio of 36:1 to 48:

1. The twin-screw extruder is provided with a main feeding functional area, a melt plasticizing functional area, an interface pre-conditioning functional area, a glass fiber side feeding functional area, a low shear dispersion functional area, a vacuum exhaust functional area and a metering extrusion functional area in sequence along the material conveying direction. The low-shear dispersion functional area is provided with a forward conveying thread element and a low-misalignment forward kneading block. The axial length of the forward conveying thread element accounts for 60-90% of the total axial length of the low-shear dispersion functional area. The misalignment angle of the low-misalignment forward kneading block is 30°-45°. The low-shear dispersion functional area is not provided with a reverse kneading block or a reverse conveying thread element. In step S5, the heat treatment temperature is 80-120℃ and the heat treatment time is 2-6h.